Co-Location, Socioeconomic Status and Perceptions of Environmental Change in the Indian Sundarbans - Dasgupta, Susmita (World Bank, Washington, DC, 2019)
Research on the determinants of collective action in the commons generally focuses on interest-group heterogeneity, implicitly assuming that groups perceive the same problems but have different priorities. This paper changes the focus to the role played by perceptions themselves. Within localities, collective action may be easier if elite and non-elite households have similar perceptions of environmental problems. Regionally, collective action may be aided by common perceptions among local elites who communicate across village lines. This paper uses regression analysis to explore variations in environmental perceptions across classes and localities, using new survey data from the Indian Sundarbans. The paper finds that perceptions vary significantly across localities. Within localities, perceptions among elite households vary significantly more than perceptions among non-elite households. The results therefore favor locally-oriented collective action in the region, along with local governance that promotes non-elite participation.